Refining the phenotype associated with biallelic DNAJC21 mutations. Issue 2 (7th June 2018) - D'Amours, G.; Lopes, F.; Gauthier, J.; Saillour, V.; Nassif, C.; Wynn, R.; Alos, N.; Leblanc, T.; Capri, Y.; Nizard, S.; Lemyre, E.; Michaud, J.L.; et al.
Abstract : Inherited bone marrow failure syndromes (IBMFS) are caused by mutations in genes involved in genomic stability. Although they may be recognized by the association of typical clinical features, variable penetrance and expressivity are common, and clinical diagnosis is often challenging. DNAJC21, which is involved in ribosome biogenesis, was recently linked to bone marrow failure. However, the specific phenotype and natural history remain to be defined. We correlate molecular data, phenotype, and clinical history of 5 unreported affected children and all individuals reported in the literature. All patients present features consistent with IBMFS: bone marrow failure, growth retardation, failure to thrive, developmental delay, recurrent infections, and skin, teeth or hair abnormalities. Additional features present in some individuals include retinal abnormalities, pancreatic insufficiency, liver cirrhosis, skeletal abnormalities, congenital hip dysplasia, joint hypermobility, and cryptorchidism. We suggest that DNAJC21 ‐related diseases constitute a distinct IBMFS, with features overlapping Shwachman‐Diamond syndrome and Dyskeratosis congenita, and additional characteristics that are specific to DNAJC21 mutations. The full phenotypic spectrum, natural history, and optimal management will require more reports. Considering the aplastic anemia, the possible increased risk for leukemia, and the multisystemic features, we provide a checklist for clinical evaluation at diagnosis and regular follow‐up. Abstract : Biallelic mutations in DNAJC21 cause features overlapping with Dyskeratosis congenita and Shwachman‐Diamond syndrome.